“KUNTUG’MISH” DOSTONI MISOLIDA O’ZBEK XALQ OG’ZAKI IJODI NAMUNALARINI O’ZBEK TILIDAN INGLIZ TILIGA TARJIMA QILISH JARAYONIDA YUZAGA KELADIGAN MUAMMOLAR TAHLILI - Asadullayeva Marjona Ziyoqul qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the analysis of the problems that arise in the process of translating the epic from Uzbek to English is considered on the example of “Kuntugmish”, one of the examples of Uzbek folklore. It is discussed what methods should be used in the translation process and what changes may occur.